2017
DOI: 10.14814/phy2.13291
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of IKKβ inhibition on the expression of E3 ubiquitin ligases and unloading-induced skeletal muscle atrophy

Abstract: We tested whether NF‐κB pathway is indispensable for the increase in expression of E3‐ligases and unloading‐induced muscle atrophy using IKKβ inhibitor IMD‐0354. Three groups of rats were used: nontreated control (C), 3 days of unloading/hindlimb suspension with (HS+IMD) or without (HS) IMD‐0354. Levels of IκBα were higher in HS+IMD (1.16‐fold) and lower in HS (0.82‐fold) when compared with C group. IMD‐0354 treatment during unloading: had no effect on loss of muscle mass; increased mRNA levels of MuRF1 and MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…We previously showed that calpain-dependent breakdown of cytoskeletal proteins plays a critical role during early stages of unloading-induced proteolysis [9]. Calpains are activated by increased calcium ions in the cytoplasm [7]. We tested whether p38α MAP kinase is also involved in the regulation of unloading-induced calpain-dependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that calpain-dependent breakdown of cytoskeletal proteins plays a critical role during early stages of unloading-induced proteolysis [9]. Calpains are activated by increased calcium ions in the cytoplasm [7]. We tested whether p38α MAP kinase is also involved in the regulation of unloading-induced calpain-dependent proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies focused on the role of Forkhead box protein O (FoxO) phosphorylation/de-phosphorylation by Akt in the regulation of E3 ubiquitin ligase expression [6]. Nevertheless, our previous studies showed that during unloading FoxO3 and NF-κB pathways do not inevitably control the upregulation of MuRF1 [7][8][9]. In some instances, different regulatory mechanisms can play the most critical role in the regulation of MuRF1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to counteract muscle atrophy in different models of wasting conditions have been recently described and include administration of β‐hydroxy β‐methylbutyrate (HMB), 1,25‐dihydroxyvitamin D, anti‐interleukin‐6 antibody treatment, IκB kinase‐β inhibition by IMD‐0354, or direct inhibition of the UPS by MG132 . In the majority of these studies, however, the pharmacological agent was administered prior to initiating muscle atrophy by hindlimb suspension or did not prevent muscle atrophy . The use of MG132 is discussed controversially with a subset of studies reporting positive effects on muscle atrophy induced by hindlimb unloading, or tumour, whereas others saw no effects .…”
Section: Discussionmentioning
confidence: 99%
“…19 This possibly relates to a diversity of underlying mechanisms, length of intervention, or pharmacokinetics, but further studies are necessary to address this in more detail. Other approaches to counteract muscle atrophy in different models of wasting conditions have been recently described and include administration of β-hydroxy β-methylbutyrate (HMB), 50 1,25-dihydroxyvitamin D, 51 anti-interleukin-6 antibody treatment, 51 IκB kinase-β inhibition by IMD-0354, 52 or direct inhibition of the UPS by MG132. [53][54][55] In the majority of these studies, however, the pharmacological agent was administered prior to initiating muscle atrophy by hindlimb suspension 51 or did not prevent muscle atrophy.…”
Section: Treatment Of Diaphragm Dysfunction and Atrophy By Compound Imentioning
confidence: 99%
See 1 more Smart Citation